2018
DOI: 10.1097/mnm.0000000000000788
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and cell proliferation in short-term and long-term effects of radioiodine-131-induced kidney damage

Abstract: Radioiodine caused cell proliferation and apoptosis as shown by immunohistochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Approximately 90% 131 I is excreted in the urine within 48 h of administration [21]. In the 131 I experimental trials, Nihat Yumusak et al [22] demonstrated that cell proliferation and apoptosis began on the seventh day and peaked during the tenth week based on the immunohistochemical analyses of the kidneys. Kolbert et al [23] provided dose-volume histograms and mean absorbed doses for 14 normal organs; the calculations were performed using a 3D voxelbased method.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% 131 I is excreted in the urine within 48 h of administration [21]. In the 131 I experimental trials, Nihat Yumusak et al [22] demonstrated that cell proliferation and apoptosis began on the seventh day and peaked during the tenth week based on the immunohistochemical analyses of the kidneys. Kolbert et al [23] provided dose-volume histograms and mean absorbed doses for 14 normal organs; the calculations were performed using a 3D voxelbased method.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed cell death, also known as apoptosis, plays a vital role in regulating the cell number of human body and function of organs31623. The major mechanism for cell injury and damage caused by ionizing radiation is regarded as being the radiation-induced apoptosis816.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% of 131 I is excreted in the urine within 48 h of administration [22]. In the 131 I experimental trials, Nihat Yumusak et al [23] demonstrated that cell proliferation and apoptosis began on the seventh day and peaked during the tenth week based on immunohistochemical analyses of the kidneys. Kolbert et al [24] provided dose-volume histograms and mean absorbed doses for 14 normal organs; the calculations were performed using a 3D voxel-based method.…”
Section: Original Papermentioning
confidence: 99%